Fluid dynamics of dinoflagellate feeding and swimming - Rudi Schuech; Lasse Tor Nielsen; Stuart Humphries; Dave Smith; Thomas Kiørboe (Limnology and Oceanography, 2025)
Flagella are crucial to the interactions of unicellular organisms with their surrounding aquatic environment. One ecologically important group of flagellates, the dinoflagellates, has a unique flagellar arrangement consisting of a trailing and a transversal flagellum. The latter is recessed within a groove around the cell and drives a hair‐bearing membrane that undulates with a helical beat. Dinoflagellates are further unique by having clearance rates that are an order of magnitude higher than those of other similarly sized phagotrophic flagellates, overlapping in size and swimming speed with ciliates. Here, using flow visualization and computational fluid dynamics, we show how this arrangement of just two flagella propels these large cells at high speeds and allows very high clearance rates. We find that the transverse flagellum provides most of the forward thrust, whereas the trailing flagellum is mainly for steering. The flagellar hairs and the sheet‐like structure of the transverse flagellum allow dinoflagellates to exert strong propulsive forces at high efficiency without extending a long flagellum far into the surrounding fluid. The unique flagellar arrangement of dinoflagellates may therefore be key to their evolutionary success.

The emerging role of alternatively activated macrophages to treat acute liver injury - Chris Humphries; Melisande L. Addison; James W. Dear; Stuart J. Forbes (Archives of Toxicology, 2025)
Acute liver injury (ALI) has a clear requirement for novel therapies. One emerging option is the use of alternatively activated macrophages (AAMs); a distinct subtype of macrophage with a role in liver injury control and repair. In this comprehensive review, we provide an overview of the current limited options for ALI, and the potential advantages offered by AAMs. We describe the evidence supporting their use from in vitro studies, pre-clinical animal studies, and human clinical trials. We suggest why the first evidence for the clinical use of AAMs is likely to be found in acetaminophen toxicity, and discuss the specific evidence for AAM use in this population, as well as potential applications for AAMs in other patient populations. The key domains by which the performance of AAMs for the treatment of ALI will be assessed are identified, and remaining challenges to the successful delivery of AAMs to clinic are explored.

Optimal Cell Length for Exploration and Exploitation in Chemotactic Planktonic Bacteria - Òscar Guadayol; Rudi Schuech; Stuart Humphries (Environmental Microbiology, 2024)
Elongated morphologies are prevalent among motile bacterioplankton in aquatic systems. This is often attributed to enhanced chemotactic ability, but how long is best? We hypothesized the existence of an optimal cell length for efficient chemotaxis resulting from shape‐imposed physical constraints acting on the trade‐off between rapid exploration versus efficient exploitation of nutrient sources. To test this hypothesis, we evaluated the chemotactic performance of elongated cephalexin‐treated Escherichia coli towards α‐methyl‐aspartate in a microfluidic device creating linear, stable and quiescent chemical gradients. Our experiments showed cells of intermediate length aggregating most tightly to the chemoattractant source. A sensitivity analysis of an Individual‐Based‐Model replicating these results showed that 1) cells of intermediate length are optimal at transient states, whereas at steady state longest cells are best, 2) poor chemotactic performance of very short cells is caused by directionality loss, and 3) long cells are penalized by brief, slow runs. Finally, we evaluated chemotactic performance of cells of different length with simulations of a phycosphere, and found that long cells swimming in a run‐and‐reverse pattern with extended runs and moderate speeds are most efficient in this microenvironment. Overall, our results suggest that the stability of the chemical landscape plays a role in cell‐size selection.

Editorial: Mechanisms and ecology of suspended-particle capture in marine systems - Jeff Shimeta; Marco Ghisalberti; Nicole Rita Posth; Stuart Humphries (Frontiers in Marine Science, 2024)

Rapid decreases in relative testes mass among monogamous birds but not in other vertebrates - Joanna Baker; Stuart Humphries; Henry Ferguson‐Gow; Andrew Meade; Chris Venditti (Ecology Letters, 2020)
Larger testes produce more sperm and therefore improve reproductive success in the face of sperm competition. Adaptation to social mating systems with relatively high and low sperm competition are therefore likely to have driven changes in relative testes size in opposing directions. Here, we combine the largest vertebrate testes mass dataset ever collected with phylogenetic approaches for measuring rates of morphological evolution to provide the first quantitative evidence for how relative testes mass has changed over time. We detect explosive radiations of testes mass diversity distributed throughout the vertebrate tree of life: bursts of rapid change have been frequent during vertebrate evolutionary history. In socially monogamous birds, there have been repeated rapid reductions in relative testes mass. We see no such pattern in other monogamous vertebrates; the prevalence of monogamy in birds may have increased opportunities for investment in alternative behaviours and physiologies allowing reduced investment in expensive testes.

Catch Composition and Selectivity of Fishing Gears in a Multi-Species Indonesian Coral Reef Fishery - Austin T. Humphries; Kelvin D. Gorospe; Paul G. Carvalho; Irfan Yulianto; Tasrif Kartawijaya; Stuart J. Campbell (Frontiers in Marine Science, 2019)

Particulate nutrient fluxes over a fringing coral reef: Source‐sink dynamics inferred from carbon to nitrogen ratios and stable isotopes - Alex S. J. Wyatt; Ryan J. Lowe; Stuart Humphries; Anya M. Waite (Limnology and Oceanography, 2013)
We examined spatial and temporal variations in particulate organic matter (POM) dynamics over a fringing coral reef (Ningaloo Reef) in Western Australia during the austral autumn and spring. Total POM concentrations generally did not differ between seasons or reef zones, but the composition of POM, in terms of carbon isotope ratios ( δ 13 C‐POM), carbon to nitrogen ratios (C : N), and fatty acids, changed consistently in water flowing across the reef. Both δ 13 C‐POM and C : N increased from the fore reef to the reef flat and lagoon, −23.0‰ to −20.1‰ and 7.31 to 8.34, respectively. Average rates of net POM uptake by the reef community were highest over the reef crest (4 to 30 mmol N m −2 d −1 and 6 to 130 mmol C m −2 d −1 ), with a Bayesian isotope model confirming independent measurements of high uptake rates of allochthonous POM (oceanic phyto‐ and zooplankton). In contrast, over the reef flat, net release of POM was observed (−4 to −5 mmol N m −2 d −1 and −50 mmol C m −2 d −1 ), with gross release rates (estimated as −6 to −8 mmol N m −2 d −1 and −30 to −90 mmol C m −2 d −1 ) indicating that the release of autochthonous POM may be of similar magnitude to allochthonous uptake. Examining POM dynamics in terms of gross fluxes reinforces the dependence of coral reef systems on oceanographic processes for allochthonous POM supply, as well as highlighting the potential for autochthonous POM production to supply nutrients to benthic and pelagic communities downstream.

Oceanographic forcing of nutrient uptake and release over a fringing coral reef - Alex S. J. Wyatt; James L. Falter; Ryan J. Lowe; Stuart Humphries; Anya M. Waite (Limnology and Oceanography, 2012)
Nitrate and nitrite (NO x ) and phosphate (PO 4 ) dynamics over Ningaloo Reef, Western Australia, are shown to depend on oceanographic forcing of coupled mass transfer limited (MTL) gross uptake and gross release from remineralized oceanic particulate organic matter (POM). Estimates of gross release rates increased significantly with increasing POM uptake and were of the same order as gross uptake rates. Gross uptake rates increased significantly with increasing oceanic concentrations and wave energy dissipation, were 35–80% higher over the reef crest (7–9 mmol NO x m −2 d −1 and 4–5 mmol PO 4 m −2 d −1 ), and were significantly correlated with independent estimates of POM‐mediated gross NO x uptake, supporting both MTL uptake and the strong role of oceanic POM supply. The relative supply of NO x and POM was linked to the seasonal dynamics of a regional current system. In late spring, upwelling associated with seasonally strong equator‐ward winds led to increased NO x concentrations (0.71 ± 0.2 µmol L −1 ), POM x and the reef was a net nutrient sink (5390 mmol NO x m −1 d −1 and 270 mmol PO 4 m −1 d −1 ). In contrast, during the autumn, NO x was low (0.16 ± 0.06 µmol L −1 ), but POM > NO x and the reef was a net nutrient source (−7060 mmol NO x m −1 d −1 and −730 mmol PO 4 m −1 d −1 ). The autumn enhancement of oceanic POM supply to the reef can be attributed to a regional phytoplankton bloom associated with acceleration of the oligotrophic Leeuwin Current, which may result in a significant supply of dissolved nutrients to downstream communities.

Can ecological and evolutionary arguments solve the riddle of the missing marine insects? - Graeme D. Ruxton; Stuart Humphries (Marine Ecology, 2008)
We critically appraise the recent literature on the paucity of marine insects and conclude that this near‐absence does demand explanation; but this explanation is unlikely to be found in the suggested problems of depth for insect respiratory systems. We tentatively suggest some areas where further consideration may yield fruitful answers to this long‐standing evolutionary riddle.

Estimation of intergenerational drift dispersal distances and mortality risk for aquatic macroinvertebrates - Stuart Humphries; Graeme D. Ruxton (Limnology and Oceanography, 2003)
Estimates of the total lifetime dispersal capacity of individuals comprising invertebrate drift in streams and rivers have proved very difficult to determine empirically. Here we use recent data on dispersal in the amphipod Gammarus pulex L. to illustrate a method for estimating the total distance an individual is likely to travel downstream during the period between hatching and its first reproductive episode. For the system we consider, this estimate is on the order of 1.5 km. This method may be useful in future explorations of the ecological relevance of within‐stream displacement and population persistence. Furthermore, we are able for the first time to estimate an upper bound for the mortality risk associated with entering the drift, which, for the G. pulex population under consideration, is less than 1% for individual drift events. We suggest that this risk may not be nearly as high as had previously been thought. These mortality and distance estimates may illustrate a fundamental difference between dispersal in lotic systems and those in other habitats, in that the mean dispersal distance is of much higher ecological relevance than that of rare long‐distance events.